Better Higgs-CP tests through information geometry - Brehmer, Johann; Plehn, Tilman; Kling, Felix (Physical review, 2018)
Measuring the CP symmetry in the Higgs sector is one of the key tasks of the LHC and a crucial ingredient for precision studies, for example in the language of effective Lagrangians. We systematically analyze which LHC signatures offer dedicated CP measurements in the Higgs-gauge sector and discuss the nature of the information they provide. Based on the Fisher information measure, we compare the maximal reach for CP-violating effects in weak boson fusion, associated ZH production, and Higgs decays into four leptons. We find a subtle balance between more theory-independent approaches and more powerful analysis channels, indicating that rigorous evidence for CP violation in the Higgs-gauge sector will likely require a multistep process.
Gesehen am 01.12.2020